PENGARUH TOTAL ASET DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP RETURN ON ASSET (ROA) BANK UMUM SYARIAH DI INDONESIA PERIODE 2018- 2022 - Rusman Azizoma; Agnes K. B. Mudamakin; Laela Sania (P3M- Politeknik Negeri Kupang, 2023)
This study aims to determine the effect of Total Assets and FDR on the ROA of Islamic Commercial Banks for the 2018-2022 period. This study uses a quantitative research method with the population in this study being all 15 Islamic Commercial Banks in Indonesia. The total sample is 54 which consists of the financial statements of Islamic Commercial Banks for 2018- 2022. The sample selection technique uses purposive sampling method. The data analysis technique used in this study is multiple linear regression. The classic assumption test technique consists of descriptive statistics, normality test, multicollinearity test, and heteroscedasticity test. Then the hypothesis test consists of the coefficient of determination, the T test to test partially, and the F test to test between variables together. The results of this study are that the Total Asset variable has a significant effect on Return On Assets (ROA) in Islamic Commercial Banks. Then the FDR variable states that the Financing To Deposit Ratio (FDR) has a positive and significant effect on the ROA of Islamic Commercial Banks. And the results of the simultaneous test state that the independent variables (Total Assets and FDR) simultaneously (together) affect the dependent variable where the dependent variable in this study is (Return On Assets).